ANALISIS PENGARUH UKURAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT (Pada Perusahaan yang Tercatat Sebagai Pemenang Dalam NCSR) - Ali Imron; Hamidah Hamidah (Jurnal Akuntansi dan Pajak, 2022)
This study aims to examine the effect of firm size and capital structure on the sustainability report. Firm size is measured by log total assets and capital structure is measured by the proportion of debt to capital. This research is a quantitative research with an explanatory research approach. The population in this study are companies that issue sustainability reports which are listed as winners in the National Center Sustainability Report (NCSR) in 2019 to 2020. This study uses purposive sampling so that 30 companies are obtained. The type of data used is secondary data obtained from the company's website. The method of data analysis is multiple regression with a significance level of 0.05, so the results of the study conclude that the firm size variable affects the publication of sustainability reporting. The capital structure variable in this study has no effect on sustainability reporting. So, the larger the size of the company, the company will publish its sustainability reporting. The goal is for external parties to know if the company has a concern for their environment. The capital structure which shows the company's debt and capital has no effect on the company's disclosure of the sustainability report.